Tracking health-related Sustainable Development Goals (SDGs) in Nepal - Meghnath Dhimal; Mandira Lamichhane Dhimal; KhemBahadur Karki; Doreen Montag; David A. Groneberg; Ulrich Kuch (Journal of Health and Social Sciences)
Sustainable Development Goals (SDGs) comprise of 17 goals and 169 targets. All SDGs are interlinked to produce synergetic eff ects and emphasize health in all policies. Among the 17 Goals, Goal 3 has a central focus on health, which is underpinned by 13 targets. The other 16 goals are also directly or indirectly related to health and will contribute to achieving the associated targets for Goal 3. The ambitious SDG agenda and their progress can be tracked by measuring numerous goals, targets, and indicators. The main objective of this paper is to provide an overview about how health- related SDGs and their targets and indicators are being tracked in the national context of Nepal. Adequate investment in research for knowledge generation, capacity building and innovation, and continous research communication among policy makers, researchers and external development partners will contribute to tracking the progress of SDGs in Nepal.